2017
DOI: 10.3390/ijms18122619
|View full text |Cite
|
Sign up to set email alerts
|

The Imbalance between n-6/n-3 Polyunsaturated Fatty Acids and Inflammatory Bowel Disease: A Comprehensive Review and Future Therapeutic Perspectives

Abstract: Eating habits have changed dramatically over the years, leading to an imbalance in the ratio of n-6/n-3 polyunsaturated fatty acids (PUFAs) in favour of n-6 PUFAs, particularly in the Western diet. Meanwhile, the incidence of inflammatory bowel disease (IBD) is increasing worldwide. Recent epidemiological data indicate the potential beneficial effect of n-3 PUFAs in ulcerative colitis (UC) prevention, whereas consumption of a higher ratio of n-6 PUFAs versus n-3 PUFAs has been associated with an increased UC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 106 publications
2
97
0
2
Order By: Relevance
“…Numerous studies prove that o-3 fatty acids and their appropriate ratio to o-6 can favourably reduce the inflammatory markers in the large intestine. erefore, many studies also indicate the beneficial effect of o-3 above all in UC [28,29]. However, fats (in total) consumed in excess may increase the risk of both CD and UC [30].…”
Section: E Influence Of Fats On the Development And Course Of Inflammmentioning
confidence: 99%
“…Numerous studies prove that o-3 fatty acids and their appropriate ratio to o-6 can favourably reduce the inflammatory markers in the large intestine. erefore, many studies also indicate the beneficial effect of o-3 above all in UC [28,29]. However, fats (in total) consumed in excess may increase the risk of both CD and UC [30].…”
Section: E Influence Of Fats On the Development And Course Of Inflammmentioning
confidence: 99%
“…Therefore, in contrast to the plasma fatty acids that reflect the recent dietary intake, the fatty acids incorporated into erythrocytes indicate the balance of these biomarkers for at least 3-4 months and, consequently, the habitual diet. 53 Although Sun et al 54 reported that the level of PUFAs from habitual dietary intake has a stronger relationship with the level of fatty acids measured in erythrocyte membranes than with those measured in the plasma, the concordance level between them is good. Therefore, in concordance with Sertoglu et al, 55 who observed that erythrocyte membrane fatty acids were superior to plasma fatty acids as biomarkers in patients with type 2 diabetes mellitus, we demonstrated in this study that erythrocyte fatty acids are associated with the stage of CKD in HD patients, as estimated by uremic toxins.…”
Section: Discussionmentioning
confidence: 99%
“…CKD is a chronic disease in which the continuous synthesis of uremic toxins and increased plasma uremic toxins directly reflect kidney failure. Therefore, in contrast to the plasma fatty acids that reflect the recent dietary intake, the fatty acids incorporated into erythrocytes indicate the balance of these biomarkers for at least 3–4 months and, consequently, the habitual diet . Although Sun et al reported that the level of PUFAs from habitual dietary intake has a stronger relationship with the level of fatty acids measured in erythrocyte membranes than with those measured in the plasma, the concordance level between them is good.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous global and national health agencies and associations and government bodies have produced many recommendations for EFA intake for a healthy human diet through fish consumption. With the advent of molecular and genetic technologies, there appeared much evidence that a balanced abundance of EFA is a prerequisite for health and disease prevention in humans [19][20][21]. Meeting the dietary demands of a burgeoning human population with a correct dietary balance of EFA and at levels required for normal health and development has become a major challenge.…”
Section: Significance and Essentiality Of Lc-pufa Biomoleculesmentioning
confidence: 99%